Chinese-Indonesian Culture: Shedjit Toapekong Cultural Carnival In Tegal City - Joseph Aldo Irawan; Liviandry Dwi Handayani; Mohammad Hiqmah Ameirindo; Ananta Budhi Danurdara (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Indonesian culture is diverse, especially in terms of culture and religion. This diversity is a positive value the community owns as a form of tolerance for diversity. One of the proofs is the existence of people of Chinese-Indonesian descent, who have lived in Indonesia since ancient times until now, one of which is in the city of Tegal. The entry of Chinese culture gave birth to a new culture that merged into a new adaptive culture in Indonesia. One such adaptive culture is shedjit toapekong. Research with qualitative descriptive methods, assisted by literature studies and supported by documentation, makes the resulting research present better results and reliable validation. The aim is to show the tolerance and collaboration of residents in the form of cultural relay activities carried out in the city of Tegal. The role of participation of all communities in this event illustrates the beauty of tolerance so that culture will continue to be maintained and can be passed on to the next generation with adaptive and collaborative results with local culture.